Pre-treatment potential of electro-coagulation process using aluminum and titanium electrodes for instant coffee processing wastewater - Hoang Quang Huy Phan; Nguyen Xuan Hoan; Nhat Huy Nguyen; Nguyen Duc Dat Duc; Nguyen Thi Ngoc Anh; Nguyen Thi Que; Nguyen Thi Thuy (Center for Science and Technology, IAIN Surakarta, 2019)
This study aimed at investigating the potential of electrocoagulation (EC) process using Al-Al and Al-Ti electrodes for the pre-treatment of instant coffee processing wastewater. Effects of various operating conditions, including cell voltage, time of treatment, inter-electrode distance, pH of solution, solution conductivity and agitation speed on the removals of chemical oxygen demand (COD) and color were considered. The maximum removal of COD and color was achieved at 87% and 99%, respectively, corresponding to COD and color in the effluents of 359-384 mg/L and 58-101 Pt-Co. Biodegradability of treated wastewater was significantly improved since BOD5/COD increased from initial value of 0.42 to 0.65 after treatment. Nether mixing nor adding of electrolyte was recommended. Moreover, the COD removal kinetics during EC process appeared to follow the first-order kinetic model. The operating costs were also determined as a reference for cost assessment of the treatment.